2019
DOI: 10.5815/ijcnis.2019.10.01
|View full text |Cite
|
Sign up to set email alerts
|

An Efficiency Optimization for Network Intrusion Detection System

Abstract: With the enormous rise in the usage of computer networks, the necessity for safeguarding these networks is also increased. Network intrusion detection systems (NIDS) are designed to monitor and inspect the activities in a network. NIDS mainly depends on the features of the input network data as these features give information on the behaviour nature of the network traffic. The irrelevant and redundant network features negatively affect the efficacy and quality of NIDS, particularly its classification accuracy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Having considered other studies in this respect, when Gu, et al [41] investigated incorporating the Self-Correlation Coefficient as the procedure of the filter method on the CICIDS2017 dataset, they could achieve the false-positive rate of 29.30. In another study, Sakr, et al [56] investigated the false-positive rates in detecting intrusions using the filter and wrapper methods. Principal Component Analysis (PCA), Correlation Feature Selection (CFS), and information gain (IG) were the procedures of the filter method; Particle Swarm Optimization (PSO) and Artificial Bee Colony (ABC) were the procedures of the wrapper method in the study by Sakr, et al [56].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Having considered other studies in this respect, when Gu, et al [41] investigated incorporating the Self-Correlation Coefficient as the procedure of the filter method on the CICIDS2017 dataset, they could achieve the false-positive rate of 29.30. In another study, Sakr, et al [56] investigated the false-positive rates in detecting intrusions using the filter and wrapper methods. Principal Component Analysis (PCA), Correlation Feature Selection (CFS), and information gain (IG) were the procedures of the filter method; Particle Swarm Optimization (PSO) and Artificial Bee Colony (ABC) were the procedures of the wrapper method in the study by Sakr, et al [56].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Sakr, et al [56] investigated the false-positive rates in detecting intrusions using the filter and wrapper methods. Principal Component Analysis (PCA), Correlation Feature Selection (CFS), and information gain (IG) were the procedures of the filter method; Particle Swarm Optimization (PSO) and Artificial Bee Colony (ABC) were the procedures of the wrapper method in the study by Sakr, et al [56]. The results of the study with respect to the obtained false-positive rates are shown in the Table 5 below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best scenario is for organizations to focus on security implementations and employee management [17]. The analysis of the human factors when focusing on internal and external attack origin, along with the ability to efficiently use anomaly detection, is vital [56]. Further understanding of human behavior research can benefit cybersecurity to provide more insights regarding the evolving challenges regarding cyber threats [20].…”
Section: Digital Crime Managementmentioning
confidence: 99%